Evaluasi Penggunaan Antibiotik pada Pasien Infeksi Saluran Kemih di RSPAU dr. S. Hardjolukito Yogyakarta Tahun 2014 - Puspitosari, Elly; , Zakky Cholisoh, M.Clin.Pharm., Ph.D., Apt (2016)
A urinary tract infection (UTI) is an infection in any part of your urinary system such as kidneys, ureters, bladder and urethra. Most infections involve the lower urinary tract, the bladder and the urethra. This type of research is an observational (non-experimental) with a descriptive study design and the data was collected by purposive sampling technique. The samples of this study were the patients who suffer from urinary tract infections in RSPAU dr. S. Hardjolukito Yogyakarta. The purpose of this study was to evaluate the accuracy of the antibiotics usage for the patients who suffer from urinary tract infections in RSPAU dr. S. Hardjolukito Yogyakarta in 2014, with the proper parameters indication, the right drug, right patient, right dosage and use standards references ofPermenkes 2014, IDSA Guideline in 2011 and Guidelines for the management of serve and septic shock in 2004 in the book of Dipiro 2008. Based on the results of this study, it is concluded that the proper indication that meet the criteria of 100% for 40 patients, the right patients 100% for 40 patients, 90% for the right medication and the right dosage for 36 patients 17.5% for 7 patients by the rational usage of antibiotics as 17.5% for 7 patients. Antibiotics which is often use is ciprofloxacin as a drug of choice